Chronic Spontaneous Urticaria Cyclosporine Treatment: Our Experience - Hilayda Karakök Güngör; Seçil Saral; Ayșenur Maden; Nihal Kundakçı; Beyza Doğanay Erdoğan; Bengü Nisa Akay (Ankara Üniversitesi Tıp Fakültesi Mecmuas)

(untitled)
Aim:Treatment of severe chronic autoimmune urticaria is difficult. In this study we aimed to investigate efficacy and safety of cyclosporine in patients with chronic urticaria.Material and Method:Twenty patients with chronic spontaneous urticaria whom detailed physical exami-nation were noted and were treated in our center between 2005 and 2013 were included in this study.Results:A total 20 patients were included in this study. Daily wheal number and number of angioedema at-tacks had been compared and significant reduce in both parameters were detected. Total duration of treat-ment was mean (min: 4, max: 144) 27,05 (±30,9507 SD, median 18) weeks. Daily cyclosporine dosages were (min: 0,54, max: 3,57), mean 2,2672 (±0,81441SD, median 2,1237). Mild hypertension was detected in two pati-ents under treatment and had been treated with anti hypertensive agents. Dyplopia was developed in 1 pati-ent. We observed elevated creatinine levels in 3 patients.Conclusion:A daily mean dosage of 2,2672 mg of cyclosporine is effective in treatment of chronic urticaria for a duration of 27 weeks. All patients must be followed up closely to monitore adverse events. Recurrence was seen in a mean 9 weeks after cessation of therapy.